Dakwah Advokasi Sosial dalam Al-Quran: Perspektif Hermeneutika Jeorge J.E. Gracia - Adnan, Abd. Mujib; Halim, Abdul (Jurnal Komunikasi Islam, 2020)
This article discusses the verses of al-Qu’ran regarding the principles of da'wah social advocacy. Using the hermeneutic approach of JE Jorge Gracia, this research has revealed that da'wah for social advocacy is an important part of Islamic teachings. The principles and scope of Islamic social advocacy are summarized in the spirit of maqashid shariah (the science of ushul fiqh), namely the defense of the basic rights of society in the framework of safeguarding religion, thought, soul, descent and property. In addition, this study also has argued that da'wah acitivist for social advocacy purposes are required to have sensitivity with regard to the efforts to solve social problems as part of fulfilling people's basic rights. Therefore, the integrity and capability of Islamic preachers who are engaged in the field of social advocacy is required.